Comprehensive Approaches of Training Organization of Project Offices Top Managers and Experts in State Management Bodies - Timur Viacheslavovich Diachkov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Implementation of project management is a new trend in public administration. Recently issued by the Government of the Russian Federation acts of project management prompted many leaders of state bodies to think about the need to train their employees the basics of the scientific organization of the project activity, and the practical aspects of the work produced by the project office. The authors reveal the mechanisms to create a comprehensive approach to the organization of training of top managers and experts of project offices in public administration based on an innovative model of management training, used in St. Petersburg.